(untitled) (Fiep Bulletin - online, 2015)
Rarely the breathing exercises used in the physiotherapy are gone back to the improvement of the breathing standard looking for to reach the Total Lung Capacity (TLC) and there are few programs that specifically approach the improvement of that pattern. However the physiotherapy is presenting significant evolution bringing benefits and could influence directly in the individuals’ breathing standard with reduction of TLC. The objective of this study was to analyze the efficiency of a program of breathing exercises in seniors with reduction of the lung oxigenate, looking for to change the breathing standard and trying to improve the treated patients’ capacity lung total. For the accomplishment of this study it was appraised four individuals, with average of 79,5 years-old age (14,5) of the feminine gender, non smokers, sedentary and presenting reduction of TLC. For each exercise of thoracic expansion were accomplished, fractional inspiration, inspiration sustained maxim, fractional expiration and diaphragm’s stimulation, during 14 sessions of 45 minutes, 5 times a week. The patients were appraised through the thoracic cirtometry, before and after each session. The data referents to the cirtometry measures were submitted the statistical analysis (tests t-student pareado). At the end of the 14 treatment sessions, it was noticed that all the participants obtained increase in the thoracic expansibility, mainly in the areas apical and basal, providing a good sensation in the patients.